Aplikasi Media Pembelajaran Ubiquitous Learning Of Angle Dengan Penerapan Pendekatan Otentik - Putra, Muhammad Trio Maulana (EDUTIC, 2023)
Covid-19 has given a new personality to education in Indonesia. The use of technology which used to be very limited, but now become an important requirement in the teaching and learning process. The learning process that used to only use blackboards or teaching aids has many limitations and can be completed by utilizing technology with media according to the subject area. Therefore, this research develops a learning media with the name "Ubiquitous Learning of Angle" which we hereinafter refer to as ULA. ULA is expected to be used by Education and Students in the teaching and learning process, especially in corner material. In developing this ULA learning media, the researcher applied the authentic approach in its application. The research methodology used in developing this application is the waterfall methodology which has 5 development processes. In the development of ULA, the hardware used was laptops and smartphones and the software used included CorelDraw, Unity3D, xampp, and Visual Studio. The outputs of this research are ULA (Ubiquitous Learning of Angle) learning media applications for students and ULA Monitoring to monitor students' learning progress.